Assessing the Overall Efficiency of two technologies of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh - Afrad, Md. Safiul Islam; Galib, Arafat Hossain; Haque, Md. Enamul; Zakaria, Mohammad; Sakib, Md. Hashmi; Rahman , Md Mahfuzur; Shoily , Afroza Awal (Journal of Extension Education, 2022)
A study was conducted to investigate the farmers’ response on the performance of two specific Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) technologies viz. BU dhan1 and BU Hybrid lau1. In this connection, two districts of Northern Bangladesh were considered with 80 farmer respondents selected by simple random sampling technique to examine their responses on technology performance, adoption, impacts, associated limitations with possible suggestions and knowledge gap. Findings from this study reveal that the BU dhan1 had a high adoption level. In contrast, BU Hybrid lau1 had a low level of adoption. BU dhan1 performed well with low complexities when it was cultivated in the field. The study further provides information that majority farmers showed low to moderate knowledge gap in cultivating both of these technologies. Moreover, dried empty grains and less market value were listed as major constraints faced by BU dhan1 growers, while BU Hybrid lau1 growers suffered from severe virus attack during cultivation. Provisions of sufficient disease-free seed supply and proper training facilities were suggested by all the farmers interviewed.